Efficacy and Safety of the Fixed Combination of Amlodipine and Valsartan in the Treatment of Arterial Hypertension and Obesity - Yakubov Abdujalol Vakhabovich; Zufarov Pulat Soatovich; Musaeva Lola Jura Kizi; Pulatova Nargiza Ikhsanovna; Akbarova Dilfuza Suratovna; Saidova Shakhnoza Oripovna; Pulatova Durdona Bahodirovna; Abdusamatova Dilorom Ziyaviddinovna (The Bioscan, 2024)
Objective: This study aimed to investigate the efficacy and safety of the fixed combination of amlodipine/valsartan in patients with mild to moderate arterial hypertension (AH) and obesity during long-term treatment. Materials and Methods: According to the protocol, 40 patients with grade I-II arterial hypertension and obesity were included in the study. All patients received a domestic combined medication Valun ("Novugen pharma," Uzbekistan) containing amlodipine 5mg and valsartan 80mg. Office blood pressure (BP) and ambulatory blood pressure monitoring (ABPM) were measured at baseline and after 12 weeks of therapy. The clinical tolerability and metabolic effects of the medication were also evaluated. Results: The 12-week therapy with the fixed combination of amlodipine and valsartan demonstrated high antihypertensive efficacy, with a 17% reduction in mean BP and achievement of the target BP level in 100% of patients with mild to moderate AH. ABPM data showed a significant reduction in average 24-hour and daytime systolic and diastolic BP values. The combined therapy with amlodipine and valsartan also exhibited nephroprotective effects, manifested by a significant decrease in blood creatinine level, an increase in glomerular filtration rate, and a reduction in microalbuminuria levels. Amlodipine and valsartan in the combined regimen showed metabolic neutrality concerning lipid and carbohydrate metabolism and clinical safety. Conclusion: Our study demonstrated the high antihypertensive efficacy of the fixed combination of amlodipine and valsartan, along with significant cardio- and nephroprotection, metabolic neutrality, and clinical safety, recommending this medication for the treatment of patients with mild to moderate arterial hypertension.